Endoscopic Fenestration of Cavum Septum Pellucidum Cysts to the Third Ventricle: Technical Note. Issue 4 (29th April 2020) - Simonin, Alexandre; Bangash, Omar; Chandran, Arjun S; Uvelius, Erik; Lind, Christopher
Abstract: BACKGROUND AND IMPORTANCE: Cavum septum pellucidum (CSP) and cavum vergae (CV) cysts are common incidental findings on imaging studies. However, they may rarely present with symptoms related to the obstruction of the foramen of Monro by the cyst leaflets. There is no consensus regarding the management of symptomatic CSP and CV cysts. We present an original transcavum interforniceal endoscopic fenestration technique. The step-by-step surgical procedure and two illustrative cases are presented. CLINICAL PRESENTATION: A 31-yr-old male and a 24-yr-old woman presented with symptomatic CSP and CV cysts. For both patients, neuronavigation was used to plan the procedure. An endoscope was introduced into the cyst through a right frontal burr-hole. After an examination of the endoscopic anatomy, a communication between the cyst and the third ventricle was performed using an endoscopic forceps. In both cases, directly after the fenestration, cerebrospinal fluid (CSF) passed through the communication, and the collapse of the cyst was appreciated. Symptoms were relieved in both patients, and neuropsychological assessment improved. Postoperative imaging showed a reduction in the cyst bulge, and patent foramen of Monro. CONCLUSION: Endoscopic fenestration of CSP and CV cysts to the third ventricle through an interforniceal navigated approach is a feasible and efficient surgical procedure. Theoretical advantages include a single tract through noneloquent brain, a perpendicular trajectory to the membrane for fenestration, and a large CSF space beyond the fenestration point.